2007
DOI: 10.2169/internalmedicine.46.1813
|View full text |Cite
|
Sign up to set email alerts
|

Doctor-Patient Communication: A Comparison betweenTelemedicine Consultation and Face-to-Face Consultation

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 14 publications
3
66
1
6
Order By: Relevance
“…This can either be between a healthcare provider and patient, or between two healthcare providers [4]. TM between healthcare providers is already in use in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…This can either be between a healthcare provider and patient, or between two healthcare providers [4]. TM between healthcare providers is already in use in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Other research have also reported a lower number of patients utterances (9) and mastery of the professional on communication (10) during consultations.…”
Section: Discussionmentioning
confidence: 83%
“…Such data also showed that, in both groups, most of the participants felt the professional understood their worries and felt confident and cared by the professionals. In other studies, the patient also evaluated the professionals clinical skills and competences in the same way in both teleconsultation and face to face consultation (9,21,23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Junto con el contexto tecnológico, que ha de propiciar más coordinación entre niveles asistenciales, el papel del profesional de enfermería de APS es un elemento clave para la mejora de los servicios de salud a la población cuidados, y si el profesional de enfermería que los utiliza los percibe como útiles 30,31 . En este contexto, parece interesante responder a la pregunta de investigación de si los profesionales de enfermería que utilizan la HCI perciben que ésta proporciona continuidad asistencial, usabilidad y permite un registro adecuado de los cuidados.…”
Section: Ae Edición Españolaunclassified